Gambaran Impostor Phenomenon Pada Mahasiswa Fakultas Psikologi Universitas Medan Area Stambuk 2018 - Maryam, Ameytha Aina; Istiana, Istiana (Jouska: Jurnal Ilmiah Psikologi, 2024)
This study aims to determine the description of the impostor phenomenon in students of the Faculty of Psychology, University of Medan Area Stambuk 2018. This study uses a quantitative descriptive research method. The subject of this research is an active student of the psychology faculty of Medan Area Class 2018 who has a minimum GPA of 3.00. The number of samples in this study were 80 people. The data collection technique in this study used a purposive sampling technique. The data collection technique used a Likert scale for the impostor phenomenon. The results of the study show that the contribution of the impostor phenomenon aspect to the students of the Faculty of Psychology, Medan University Area, Class 2018 is fake by 52.68%, luck by 16.70% and discount by 30.59%. This means that fake is the aspect of the impostor phenomenon that contributes the largest contribution while luck is the aspect of the impostor phenomenon that contributes the lowest contribution in this study. Based on the results of the calculation of the hypothetical mean on the impostor phenomenon variable with 5 answer choices, the result is 48,000. The empirical mean of the impostor phenomenon as a whole is 46.550 with SD = 7.960. The results of the analysis show that in general students of the Faculty of Psychology, University of Medan Area Class 2018 have a moderate level of the impostor phenomenon.